The Immediate And Intermediate Results Of Percutaneous Balloon Aortic Valvuloplasty In Patients With Congenital Valvular Aortic Stenosis - Alwahab, Hussein A. (AL-Kindy College Medical Journal, 2019)
Background: Aortic valve stenosis results from minor to severe degrees of aortic valve maldevelopment. This stenosis causes mild to severe obstruction of the left ventricular outflow . Objectives : to study the immediate and intermediate results of percutaneous balloon aortic valvuloplasty in patients with congenital valvular aortic stenosis . Type of the study: A prospective study. Methods: The study was done on thirty five patients with congenital valvular aortic stenosis who had percutaneous balloon aortic valvuloplasty in Ibn Al- Bitar Center for Cardiac Surgery from May 2009 to February 2011. Results: Twenty seven patients were male (77.2%) and 8 patients were female (22.8%), male to female ratio 3.5/ 1, . The aortic valve was bicuspid in 18 patients (51.4%) while 17 patients ( 48.6%) had tricuspid aortic valve. Balloon aortic valvuloplasty was successful in 30 patients (85.7%),. Maximum peak instantaneous Doppler pressure gradient across the aortic valve 24 hours postprocedural echocardiography showed reduction which is statistically significant. New aortic regurgitation had occurred in 15 patients ( 42.8%), it was mild in 9 patients ( 25.6%), moderate in 5 patients ( 14.3%) and severe in 1 patient( 2.9%) which is statistically significant. The follow up of 12.57 ± 3.88 ( 3- 22) months after intervention was done for all patients using echocardiography Doppler study, reveal the maximum peak instantaneous Doppler pressure gradient across the aortic valve was raised which is statistically significant. The aortic regurgitation was present in 18 patients (51.4%) , it was mild in 9 patients (25.7%) , moderate in 6 patients (17.1%) and severe in 3 patients ( 8.6%). No mortality had been reported during the procedure or on follow up. Conclusion: Aortic balloon valvuloplasty is safe and effective procedure in the treatment of congenital valvular aortic stenosis but mild aortic regurgitation is the most common immediate complication of aortic balloon dilatation and progressive aortic regurgitation is a major problem during the intermediate follow up.